Compliance of “Principles of transparency and best practice in scholarly publishing” in academic society published journals - Hyung Wook Choi; Ye Jin Choi; Soon Kim (Science Editing, 2019)
Purpose Four international associations, including the Open Access Scholarly Publishers Association, the Directory of Open Access Journals, the Committee on Publication Ethics, and the World Association of Medical Editors declared the third version of “Principles of transparency and best practice in scholarly publishing” to ensure transparency and quality in journal publications. This study is aimed at assessing the guidelines from the journals’ websites manually. Methods In this study, three researchers investigate the homepages of 781 academic society-published journals that are registered in the Science Citation Index Expanded and whether these journals are effectively adopting these new guidelines. In this paper, 33 items from the guidelines are examined. The 33 items are rearranged into four different categories: basic journal information; publication ethics; copyright and archiving information; and profit model. The researchers count yes or no after checking the adopting status on the journal homepage and dividing into four scales: 0% to 25% for is rarely practiced, 26% to 50% for is poorly practiced, 51% to 75% for is adequately practiced, and 76% to 100% for is well practiced. Results Of the 33 items, 10 are found to be poorly or rarely practiced, including readership, data sharing, archiving policies, and profit model information. Conclusion It could be the most up-to-date indicator of the current status of applying best practice guidelines. Society journal editors especially from Asia should evaluate their journals regarding “Principles of transparency and best practice in scholarly publishing”.